Peningkatan Perekonomian Masyarakat Pedesaan Melalui Kemitraan Koperasi Desa - Wiwin, Wiwin; Nahhuda, Nahuda; Sekarini, Ratih Ayu; Chotimah, Siti (Politeknik Negeri Medan, 2021)
Community service outreach activities based on research results, the theme of the activity is improving the economy of rural communities through cooperative partnerships, carried out in the form of counseling and socialization with the aim of providing understanding and the spirit of cooperatives to the community. Where the cooperative, is an economic business that is a pillar of the national economy which has the aim of prospering its members in particular and society in general. Pasirjambu Village, Pasirjambu Sub-district, Bandung Regency is a Partner Village (Guidance) for the Community Service Institute, Jakarta Islamic University. The active cooperatives are KSP Sejahtera and KSP PWRI. The existence of the cooperative is proven by research that still needs to be improved and expanded its partnership network, and the community in Pasirjambu Village has not yet felt the positive impact. Therefore, there is a need for continuous counseling, mentoring, and socialization in order to take advantage of the existing potential in order to help improve the local economy through cooperatives. The method of activity is counseling, filling out questionnaires, delivering material, socializing discussions asking questions and mentoring. The results of outreach activities and socialization of community service are that the community can understand cooperatively in a comprehensive manner, so that they have a strong desire to become active members, collaborate in mentoring and establish sustainable collaboration. Kegiatan penyuluhan Pengabdian kepada masyarakat berbasis hasil penelitian, tema kegiatan yaitu peningkatan perekonomian masyarakat pedesaan melalui kemitraan koperasi, dilaksanakan dalam bentuk penyuluhan dan sosialisasi dengan tujuan memberikan pemahaman dan semangat berkoperasi kepada masyarakat. Dimana koperasi, merupakan sebagai usaha ekonomi yang menjadi pilar perekonomian nasional yang memiliki tujuan untuk mensejahterakan para anggota khususnya dan masyarakat pada umumnya. Desa Pasirjambu Kecamatan Pasirjambu Kabupaten Bandung merupakan Desa Mitra (Binaan) Lembaga Pengabdian kepada Masyarakat Universitas Islam Jakarta. Koperasi yang aktif KSP Sejahtera dan KSP PWRI. Keberadaan koperasi tersebut dibuktikan dengan penelitian masih perlu ditingkatkan dan diperluas jejaring kemitraannya, dan masyarakat di Desa Pasirjambu belum cukup merasakan dampak positif. Oleh karena itu, perlu adanya penyuluhan, pendampingan dan sosialisasi yang berkesinambungan guna memanfaatkan potensi yang ada dalam rangka membantu meningkatkan perekonomian daerah setempat melalui koperasi. Metode kegiatan yaitu penyuluhan, pengisian angket, penyampaian materi, sosialisasi diskusi dan tanya jawab serta pendampingan. Hasil kegiatan penyuluhan dan sosialisasi pengabdian kepada masyarakat yaitu masyarakat dapat memahami tentang koperasi secara komprehenship, sehingga memiliki keinginan yang kuat menjadi anggota aktif, kolaborasi pendampingan dan terjalin kerjasama yang berkelanjutan.